Costs of switching to low global warming potential inhalers. An economic and carbon footprint analysis of NHS prescription data in England. Issue 10 (29th October 2019) - Wilkinson, Alexander J K; Braggins, Rory; Steinbach, Ingeborg; Smith, James
Abstract : Objectives: Metered-dose inhalers (MDIs) contain propellants which are potent greenhouse gases. Many agencies propose a switch to alternative, low global warming potential (GWP) inhalers, such as dry powder inhalers (DPIs). We aimed to analyse the impact on greenhouse gas emissions and drug costs of making this switch. Setting: We studied National Health Service prescription data from England in 2017 and collated carbon footprint data on inhalers commonly used in England. Design: Inhalers were separated into different categories according to their mechanisms of action (eg, short-acting beta-agonist). Within each category we identified low and high GWP inhalers and calculated the cost and carbon impact of changing to low GWP inhalers. We modelled scenarios for swapping proportionally according to the current market share of each equivalent DPI (model 1) and switching to the lowest cost pharmaceutically equivalent DPI (model 2). We also reviewed available data on the carbon footprint of inhalers from scientific publications, independently certified reports and patents to provide more accurate carbon footprint information on different types of inhalers. Results: If MDIs using HFA propellant are replaced with the cheapest equivalent DPI, then for every 10% of MDIs changed to DPIs, drug costs decrease by £8.2M annually. However if the brands of DPIs stay the same as 2017 prescribing patterns, for every 10% of MDIs changed to DPIs, drug costs increase by £12.7M annually. Most potential savings are due to less expensive long-acting beta-agonist (LABA)/inhaled corticosteroids (ICS) inhalers. Some reliever inhalers (eg, Ventolin) have a carbon footprint over 25 kg CO2 e per inhaler, while others use far less 1, 1, 1, 2-tetrafluoroethane (HFA134a) (eg, Salamol) with a carbon footprint of <10 kg CO2 e per inhaler. 1, 1, 1, 2, 3, 3, 3-Heptafluoropropane (HFA227ea) LABA/ICS inhalers (eg, Flutiform) have a carbon footprint over 36 kg CO2 e, compared with an equivalent HFA134a combination inhaler (eg, Fostair) at <20 kg CO2 e. For every 10% of MDIs changed to DPIs, 58 kt CO2 e could be saved annually in England. Conclusions: Switching to DPIs would result in large carbon savings and can be achieved alongside reduced drug costs by using less expensive brands. Substantial carbon savings can be made by using small volume HFA134a MDIs, in preference to large volume HFA134a MDIs, or those containing HFA227ea as a propellant.